Seed ecology and seedling dynamics of western Himalayan treeline tree species - Singh, Nandan; Tewari, Ashish; Mittal, Amit; Shah, Shruti; Bisht, Mamta; Siddiqui, Sazada; Alshaharni, Mohammed O.; Saddiqua, Ayesha (Frontiers in Forests and Global Change, 2024)
Several high-elevation plant species would experience an increased risk of regional extinction due to various climatic and anthropogenic factors. Information about the effects of climate change is urgently needed for modeling vegetation dynamics because it influences the various seed parameters like seed germination, seed maturation, seed mass, and seed bank in the soil. The present study was conducted at an elevation of 3145–3560 m in the treeline area of the western Himalayan region of India. The change in seed color is correlated with other seed parameters such as seed moisture content, seed germination, seed mass, and seed fall density. A decline in moisture content in maturing seeds is closely related to seed maturity (p < 0.05). Quercus semecarpifolia contains the highest seed mass followed by Abies spectabilis. Reportedly, the species with higher seed mass have an advantage in light-restricted environments for seed germination and seedling development. In addition, the fruit mass was observed to be the highest for Rhododendron campanulatum, while both Betula utilis and R. arboreum had similar fruit mass. The seed fall density varied between 1.55 and 7.85 seeds m–2 and the maximum mortality of up to 32% of seedlings was observed during post-monsoon season from November to February. The potential disruption in the timing of seed fall, soil seed bank, and seed germination due to climatic irregularities has broader implications for forest ecosystems. Generally, the soil in treeline areas gets frozen during winter, resulting in seedlings facing severe water stress and a high rate of transpiration. The present study addresses the issue regarding the survival and proliferation of important treeline species in the western Himalayan region of India.